A novel lncRNA AC112721.1 promotes the progression of triple-negative breast cancer by directly binding to THBS1 and regulating miR-491-5p/C2CD2L axis - Ping Ma; Shiyao Kang; Huimin Li; Ming Li; Yuan Zhao; Hongjun Yuan; Jianyu Pang; Wenru Tang; Miaomiao Sheng (Scientific Reports)
Abstract Triple-negative breast cancer (TNBC) seriously threatens women’s health, and long noncoding RNAs (lncRNAs) are emerging as critical regulators of gene expression and play fundamental roles in TNBC. This study aimed to identify lncRNAs that represent effective targets for the early diagnosis or treatment of TNBC. Here, we utilized the TCGA database to analyze differentially expressed genes, and survival analysis and ROC curve analysis were also performed. Notably, we identified a novel lncRNA, AC112721.1, that is significantly overexpressed in TNBC and is associated with poor overall survival in TNBC patients. Loss- and gain-of-function experiments revealed that AC112721.1 significantly promoted cell proliferation and migration, suppressed cell apoptosis in vitro and inhibited tumorigenesis in vivo. Further study of the mechanisms underlying these effects revealed that AC112721.1 regulates the Ras pathway by directly binding to THBS1 protein and functions as a ceRNA by sponging miR-491-5p to increase the expression of C2CD2L, thereby influencing the progression of TNBC. Our findings indicate that AC112721.1 may represent a new biomarker for evaluating TNBC prognosis and treating TNBC.